SPE Annual Technical Conference and Exhibition 1999
DOI: 10.2118/56421-ms
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Transient Analysis of Perforated Slant and Horizontal Wells

Abstract: This paper was prepared for presentation at the 1999 SPE Annual Technical Conference and Exhibition held in Houston, Texas, 3–6 October 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…In a previous study, 32 it was shown that the transients caused by the convergence of streamlines around perforations dies out very fast. Hence, the energy loss caused by convergent flow into perforation tunnels can be represented as an additional stabilized pressure drop beyond very early times.…”
Section: Flow Model For Perforated Horizontal Wellmentioning
confidence: 93%
See 3 more Smart Citations
“…In a previous study, 32 it was shown that the transients caused by the convergence of streamlines around perforations dies out very fast. Hence, the energy loss caused by convergent flow into perforation tunnels can be represented as an additional stabilized pressure drop beyond very early times.…”
Section: Flow Model For Perforated Horizontal Wellmentioning
confidence: 93%
“…[27][28][29][30][31][32][33][34] Landman and Goldthorpe 27 and Marett and Landman 28 presented steady-state models for flow into perforations distributed around a horizontal wellbore. They also proposed the use of variable perforation shot density to obtain a uniform influx along the wellbore.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[27][28][29][30][31][32][33][34] Landman and Goldthorpe 27 presented a steady state model for flow into perforations distributed around a horizontal wellbore. Their model accounts for wellbore pressure drop but considers an infinitely large reservoir in all directions and treats the neighboring perforations as point sinks.…”
Section: Introductionmentioning
confidence: 99%